2015
DOI: 10.1378/chest.14-1934
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Air Dispersion During Noninvasive Ventilation via Helmets and a Total Facemask

Abstract: A helmet with a good seal around the neck is needed to prevent nosocomial infection during NIV for patients with respiratory infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
129
0
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(142 citation statements)
references
References 36 publications
5
129
0
8
Order By: Relevance
“…32 Broad dispersion of exhaled air during NIV via a face mask has previously been shown using a simulated patient encounter. 33 Although NIV was successfully used in a small number of SARS patients without documented nosocomial transmission, 13 other studies showed that NIV might have led to increased nosocomial transmission. 16,34 In our cohort, NIV failure was strikingly high and was associated with more requirements for inhaled nitric oxide.…”
Section: Discussionmentioning
confidence: 99%
“…32 Broad dispersion of exhaled air during NIV via a face mask has previously been shown using a simulated patient encounter. 33 Although NIV was successfully used in a small number of SARS patients without documented nosocomial transmission, 13 other studies showed that NIV might have led to increased nosocomial transmission. 16,34 In our cohort, NIV failure was strikingly high and was associated with more requirements for inhaled nitric oxide.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, water content in the respiratory droplets may be evaporated and hence produce small droplet nuclei that are suspended in air. Nevertheless, the smoke particles used in this study mark the continuous air phase, and therefore our data indicated the anticipated "upper limits" of droplet dispersion [10][11][12][13][14][15][16]21 .…”
Section: Discussionmentioning
confidence: 54%
“…Our research team of investigators, consisting of a respiratory physician, an anesthesiologist/intensivist, and an aerodynamic architect that have jointly conducted and published a series of infection control experiments on a HPS (HPS 6.1, CAE Healthcare, Sarasota, FL) to display exhaled air dispersion quantitatively using a laser visualization technique during application of common respiratory therapies in different hospital ventilation settings [10][11][12][13][14][15][16] . In this study, we characterized the pattern of dispersion of potentially infected aerosols during two commonly performed procedures during resuscitation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations